Anti-Inflammatory Activity Test of Ethanol Extract of Kencur Rhizome (Kaempferia galanga L.) on Male White Mice (Mus musculus L.) Induced Carrageenan - Khasanah, Nisfi Lailatul; Riyanta, Aldi Budi; Susiyarti, Susiyarti (Journal of Experimental and Clinical Pharmacy (JECP), 2024)
Inflammation needs to be addressed, considering that inflammation is a local protective response caused by tissue damage. This condition can indeed be overcome by consuming chemical drugs, one of which is in the NSAIDS group, namely diclofenac sodium, but chemical drugs have many negative effects, including nonsteroidal anti-inflammatory drugs and steroids. Therefore, there has been the creation of anti-inflammatory drugs using natural ingredients, especially plants. For generations, Indonesian people have used kencur as an edema medicine. This study aims to examine the anti-inflammatory properties of kencur ethanol extract rhizomes. This study tested anti-inflammatory activity through regeninduced suppression of foot edema in male white mice. In this study, 15 eligible mice aged 2–3 months and weighing 20–30 grams were divided into 5 treatment groups. Three separate doses of galangal rhizome extract—50 mg/kgBW, 150 mg/kgBW, and 250 mg/kgBW—were used in the test. Ethanol extract of kencur rhizomes at a dose of 250 mg/kgBW can reduce edema in male white mice produced by carrageenan by 1% and show possible anti-inflammatory properties, according to the results of studies tested by measuring edema using a digital caliper.